Avaliação técnico-econômica da produção de frio a partir de concentrador solar : um estudo de caso para o semiárido brasileiro - Alves, Fernando Pinheiro (2018)
The Brazilian semiarid is a region that presents a high incident solar irradiation and its main economic activity is the farming. Therefore, this work has the objective of evaluating the technical and economic potential of the implementation of solar concentrators to take advantage of this solar resource of the region to supply the refrigeration demand from a fruit distributor. A vapor compression refrigeration cycle, which needs electricity supply, and an absorption refrigeration cycle, which doesn’t need electricity supply, were simulated to verify which system is most economically feasible. The thermal demand was calculated from heat transfer equations using real data from a local distributor. The simulations of the cooling cycles and the solar fields were made using the softwares Hysys and System Advisor Model, respectively. The results indicated that the vapor compression system is more economically feasible, even though electricity production is necessary, because of its higher coefficient of performance.